Rancang Bangun Alat Penyiram Otomatis Menggunakan Sensor Kelembaban Tanah Berbasis Mikrokontoler pada Tanaman Kopi - Suparman, Suparman; Puruhito, Dimas Deworo; Dharmawati, Nuraeni Dwi; Pinandito, Ksatriyo; Putri, Ayunda Gustiani (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
This research activity was carried out on coffee farmer groups in Mandan Sucen Gemawang Temanggung which emphasized the design of automatic sprinklers using microcontroller-based soil moisture sensors for coffee plants. Coffee plants need enough water for their growth. Manually sprinkling coffee plants requires sufficient resources, the problem is that there are human limitations in helping with maintenance and it takes quite a long time. The purpose of this research is to help coffee farmers by designing coffee sprinklers automatically. The research method used to complete this research is Research and Development which includes tool planning, tool design, tool testing, and analysis of an automatic plant watering system using a microcontroller-based soil moisture sensor on YL-69 type coffee plants. The output of the research is a prototype of an automatic plant sprinkler system using sensors, microcontrollers, relays and a 16x2 LCD display screen. From the calibration results, the accuracy of the tool is 97.41% and the error is 2.59%. This system can monitor and control the water requirements of coffee plants and automatic watering is carried out when the soil moisture is < 40%, the pump will start automatically and the pump will automatically turn off when the soil moisture is > 60%. The conclusion from the results of this study is that there is a sprinkler automatically using a microcontroller-based soil moisture sensor to assist coffee farmer groups in Mandan Sucen Gemawang Temanggung in watering coffee.